Risk Factors of Preterm Birth in Nepal: A Hospital-Based Matched Case-Control Study - Acharya, Richa; Khanal, Pratik; Bhattarai, Hari Krishna; Amatya, Archana (Frontiers in Reproductive Health, 2021)
Background: Preterm birth is a significant cause of neonatal death globally. Nepal is in the 20th position in the world, with the highest rate of preterm deliveries. The risk factors of preterm birth have not been fully identified and established in Nepal. The study aims to identify risk factors of preterm birth among women who underwent delivery in a tertiary maternal hospital in Nepal. Methods: This study employed a hospital-based matched case-control study design. The case included women who delivered before 37 weeks of gestation, and women who delivered between 37 and 42 weeks of gestation served as controls. The ratio of the case to control was 1:2, and matching was done for the type of delivery. The first author collected the data in the Paropakar Maternity and Women's Hospital between December 2015 and January 2016. Face-to-face interviews were conducted using a structured questionnaire. Backward conditional logistic regression was performed to identify the independent risk factors of preterm birth. Results: Antihelminthic treatment during pregnancy was found to be protective for preterm birth. Women performing intensive physical work during their pregnancy and women exposed to indoor air pollution were more likely to have a preterm birth than women not performing intensive physical work and women not exposed to indoor pollution, respectively. Conclusions: Women who had not consumed antihelminthic drugs per protocol, those exposed to indoor air pollution, and those who performed intensive work during pregnancy were at higher risk for preterm birth. Maternal health programs can encourage women to consume antihelminthic drugs, take proper rest during pregnancy, and prevent indoor pollution exposure.